The Calculus of Computation Decision Procedures with Applications to Verification - Bradley, Aaron R.; Manna, Zohar (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Computational logic is a fast-growing field with applications in artificial intelligence, constraint solving, and the design and verification of software and hardware systems. Written with graduate and advanced undergraduate students in mind, this textbook introduces computational logic from the foundations of first-order logic to state-of-the-art decision procedures for arithmetic, data structures, and combination theories. This textbook also presents a logical approach to engineering correct software. The increasing ubiquity of computers makes implementing correct systems more important than ever. Verification exercises develop the reader's facility in specifying and verifying software using logic. The treatment of verification concludes with an introduction to the static analysis of software, an important component of modern verification systems. For readers interested in learning more about computational logic, decision procedures, verification, and other areas of formal methods, the final chapter outlines courses of further study.